PENGARUH LATIHAN FISIK AEROBIK TERHADAP WARNA DAN KEJERNIHAN URIN PADA PENDERITA HIPERTENSI - Nurna Ningsih (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2020)
Background: Hypertension causes various complications, disability and death. One way to control blood pressure that can be done by people with hypertension is aerobic exercise. Aerobic physical exercise can risk causing dehydration, for that during physical exercise it is necessary to consider fluid intake during aerobic physical exercise so that the expected benefits are obtained. Methods: This study aims to determine the categories of color and clarity of urine before and after aerobic physical exercise in patients with hypertension. This research method is pre-experimental with one group pre-Post Design, the intervention runs fast as far as 2.25 km in 30 minutes in the work area of the Gandus Health Center, Palembang city in 2014. Sampling uses a purposive sampling technique totaling 20 respondents. Measurement of the color and clarity of urine is carried out by experts in the laboratory. Different test uses marginal homogenity. Results: Most respondents aged between 46-47 years were 75%, women 75%, mild dehydration 30%. Yellow urine before and after aerobics is 90% yellow, after 85%, while 5% urine clarity has changed from slightly cloudy to cloudy. Statistical test results found no significant differences between color (p = 0.157) and urinary clarity (p = 0.317) before and after aerobic physical exercise. Conclusion: Aerobic physical exercise with fast walking does not affect the color and clarity of urine in people with hypertension. Future researchers are expected to conduct a similar study using a control group.